Fresh ingredients healthy international foods tips - Mitchell, Brett; Mitchell, Paulette; Learning ZoneXpress (Firm). ([United States] : Learning Zonexpress, 2011)
Cookbook author and world traveler Paulette Mitchell presents a series of food and nutrition lessons from food markets around the world that can be applied to home-cooked meals. She contrasts packaged and processed foods with similar fresh items found at local farmer's markets and supermarkets, while offering tips for using fresh, tasty ingredients in quick-to-prepare, healthful meals -- container.
For audience grade 6 - Adult.
DVD format.
Keywords: Food; Food handling